The Stock Price Determinants: The Effect of Inflation, Interest Rates, and EPS on the Basic Industry and Chemical Sector of the Indonesian Stock Exchange (IDX) 2021-2024 - Marli (LP2M IAIN Palopo, 2025)
This study aims to analyze the effect of Earnings Per Share (EPS), Inflation, and Interest Rates on Stock Prices using the Partial Least Square Structural Equation Modeling (PLS-SEM) approach. Data were analyzed through a significance test with bootstrapping techniques to determine the causal relationship between latent variables. The results showed that EPS has the most dominant positive effect on stock prices with a path coefficient of 0.878 (T-statistic = 15.597, p-value = 0.000), indicating that company financial performance is the main factor in determining stock prices. Interest Rates also showed a significant positive effect (coefficient = 0.124, T-statistic = 3.527, p-value = 0.000), although with a lower magnitude. Conversely, Inflation did not have a significant effect on stock prices (coefficient = -0.059, p-value = 0.135), so the hypothesis regarding the effect of inflation was rejected. The research model demonstrated excellent predictive power with an R-Square value of 0.758, meaning that approximately 75.8% of the stock price variation can be explained by the three independent variables. This finding provides important implications for investors in making investment decisions and for company management in strategies to increase company value through optimizing financial performance .